Lenkų kalba ir žemaičių bajorai XX a. pirmoje pusėje - Adomavičiūtė-Čekmonienė, Irena Elžbieta (Kalbotyra, 1997)
The tradition of usage of the Polish language by the so called ‘bajorai’ (gentry) in one small area in the south-west part of Žemaitia is described in the article. A sociolinguistic investigation has been carried out in 15 small villages around the tiny town of Skaudvilė. It is shown that the Polish language was a cultural, socially prestigious dialect for the traditional gentry and was not associated with their national consciousness. The pre-war period of the Lithuanian Republic’s history was highly unfavourable for the so-called Polish-Lithuanian gentry because of the development of the new Lithuanian national consciousness that was acutely opposed to the very idea of possibility to can Lithuanians those who traditionally spoke Polish, as it was in case of gentry with their XIX c. well-known self-awareness as “gente Lituani, Natione Poloni”. Those of them who survived Soviet repression on survived at all do not speak Polish these days, but there are many Polish borrowings in their Lithuanian speech.